2021
DOI: 10.1186/s13071-021-04906-z
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of kdr mutations correlated with the temperature in field populations of Aedes albopictus in China

Abstract: Background Aedes albopictus is the primary vector of dengue fever in China. This mosquito species has a wide distribution range in China and can be found in the tropical climate zones of southern provinces through to temperate climate zones of northern provinces. Insecticides are an important control method, especially during outbreaks of dengue fever, but increasing insecticide resistance raises the risk of failure to control vector-borne diseases. Knockdown resistance (kdr) caused by point mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 32 publications
2
26
1
Order By: Relevance
“…The high allelic diversity and expected heterozygosity were observed in most of the populations (H O = 0.32-0.57), which was similar to the level of diversity in the Ae. albopictus of the coastal areas in southern China (H O = 0.384-0.641) [23], and 17 populations from 3 climatic regions of China (H O = 0.467-0.627) [ Notably, the F ST value of GDST population was minimum (0.087), meanwhile carrying no mutation in F1534 [34]. As the collection site is close to the seaside wharf, therefore it was speculated that GDST population mosquito was imported from ships and colonized locally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high allelic diversity and expected heterozygosity were observed in most of the populations (H O = 0.32-0.57), which was similar to the level of diversity in the Ae. albopictus of the coastal areas in southern China (H O = 0.384-0.641) [23], and 17 populations from 3 climatic regions of China (H O = 0.467-0.627) [ Notably, the F ST value of GDST population was minimum (0.087), meanwhile carrying no mutation in F1534 [34]. As the collection site is close to the seaside wharf, therefore it was speculated that GDST population mosquito was imported from ships and colonized locally.…”
Section: Discussionmentioning
confidence: 99%
“…albopictus in China and signi cantly associated with pyrethroid resistance phenotype [54]. The frequency of F1534S was obtained from our published literature [34], which populations were the same as the theses samples. Pearson correlation coe cient R was used to examine the association between the two variables and was calculated by SPSS 20.0 (IBM Corp., Armonk, NY, USA).…”
Section: Correlation Between Genetic Variation Within Population and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies state that temperature is the most important ecological factor affecting the physiology of Aedes species, in addition to the gonotrophic cycle length and the survival rate of adults (Brady et al, 2014). Chen et al (Chen et al, 2021) analyzed the correlation between annual average temperature, and kdr mutations, indicating that temperature possibly affects insecticide resistance. In addition, it has been reported that multiple loci mutations in the VGSC gene can simultaneously increase the level of resistance (Plernsub et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite studies having so far mostly focused on major vector species, in the last decade a few mutations within the vssc gene have also been identified in Ae. albopictus, in particular in positions 1534 (F1534C/S/L/W/R; [19,[33][34][35][36]), 1016 (V1016G/I [34,36,37]) and 1532 (I1532T [38]). Among these, the only alleles confirmed to be associated with strong pyrethroid resistance phenotypes are 1534C [37], 1534S [18,36,37,39] and 1016G [29,37].…”
Section: Introductionmentioning
confidence: 99%